APPROACHES TO INTERPRETER EDUCATION: INTEGRATING INTERPRETING AND TRANSLATION IN THE LANGUAGE CLASSROOM (KONFERENSIYA, 2025)
This article presents a comprehensive, practice-informed roadmap for weaving interpreting and translation into general language education. Treating the two as complementary, not competing, it argues that mediation-oriented pedagogy accelerates communicative competence, intercultural literacy, and career readiness. I synthesize foundational theories with classroom-tested routines, propose level-specific outcomes and task sequences, and offer assessment models that center transparency and formative growth. Special attention is given to cognitive load, authenticity, ethics, and inclusivity, with pragmatic solutions for teachers who may not be specialist trainers but seek to build robust mediation pathways